Treatment Effects of Interleukin-6 Receptor Antibodies for Modulating the Systemic Inflammatory Response After Out-of-Hospital Cardiac Arrest (The IMICA Trial): A Double-Blinded, Placebo-Controlled, Single-Center, Randomized, Clinical Trial. Issue 19 (11th May 2021) - Meyer, Martin Abild Stengaard; Wiberg, Sebastian; Grand, Johannes; Meyer, Anna Sina Pettersson; Obling, Laust Emil Roelsgaard; Frydland, Martin; Thomsen, Jakob Hartvig; Josiassen, Jakob; Møller, Jacob Eifer; Kjaergaard, Jesper; Hassager, Christian
Abstract : Background: Patients experiencing out-of-hospital cardiac arrest who remain comatose after initial resuscitation are at high risk of morbidity and mortality attributable to the ensuing post–cardiac arrest syndrome. Systemic inflammation constitutes a major component of post–cardiac arrest syndrome, and IL-6 (interleukin-6) levels are associated with post–cardiac arrest syndrome severity. The IL-6 receptor antagonist tocilizumab could potentially dampen inflammation in post–cardiac arrest syndrome. The objective of the present trial was to determine the efficacy of tocilizumab to reduce systemic inflammation after out-of-hospital cardiac arrest of a presumed cardiac cause and thereby potentially mitigate organ injury. Methods: Eighty comatose patients with out-of-hospital cardiac arrest were randomly assigned 1:1 in a double-blinded placebo-controlled trial to a single infusion of tocilizumab or placebo in addition to standard of care including targeted temperature management. Blood samples were sequentially drawn during the initial 72 hours. The primary end point was the reduction in C-reactive protein response from baseline until 72 hours in patients treated with tocilizumab evaluated by mixed-model analysis for a treatment-by-time interaction. Secondary end points (main) were the marker of inflammation: leukocytes; the markers of myocardial injury: creatine kinase myocardial band, troponin T, and N-terminal pro B-type natriuretic peptide; and the marker of brain injury: neuron-specific enolase. These secondary end points were analyzed by mixed-model analysis. Results: The primary end point of reducing the C-reactive protein response by tocilizumab was achieved since there was a significant treatment-by-time interaction, P <0.0001, and a profound effect on C-reactive protein levels. Systemic inflammation was reduced by treatment with tocilizumab because both C-reactive protein and leukocyte levels were markedly reduced, tocilizumab versus placebo at 24 hours: –84% [–90%; –76%] and –34% [–46%; –19%], respectively, both P <0.001. Myocardial injury was also reduced, documented by reductions in creatine kinase myocardial band and troponin T; tocilizumab versus placebo at 12 hours: –36% [–54%; –11%] and –38% [–53%; –19%], respectively, both P <0.01. N-terminal pro B-type natriuretic peptide was similarly reduced by active treatment; tocilizumab versus placebo at 48 hours: –65% [–80%; –41%], P <0.001. There were no differences in survival or neurological outcome. Conclusions: Treatment with tocilizumab resulted in a significant reduction in systemic inflammation and myocardial injury in comatose patients resuscitated from out-of-hospital cardiac arrest. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03863015. Abstract : Supplemental Digital Content is available in the text.